The bismuth subiodides Bi8Pt5I3 and Bi16Pt11I6 - Layered metals with covalent platinum networks - Rasche, Bertold; Schnelle, Walter; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
Black shiny platelets of Bi8Pt5I3 and Bi16Pt11I6 were crystallized from melts of the metals and BiI3. Despite very similar compositions and close peritectics, a protocol for targeted synthesis could be developed based on differences of the decomposition pressures. Bi8Pt5I3 has a monoclinic crystal structure [space group C2/m; a = 1850.7(2) pm, b = 391.46(3) pm, c = 1340.5(1) pm, β = 113.28(1)°], in which corrugated intermetallic layers alternate with monolayers of non-coordinating iodide ions. The platinum atoms are in square, trigonal-prismatic, or capped trigonal-prismatic coordination by bismuth atoms. Additional covalent bonding between platinum atoms defines flat stripes of five atoms width inside the intermetallic layer. Bi16Pt11I6 crystallizes in the acentric tetragonal space group P4212 with a = 1386.6(1) pm and c = 924.5(1) pm. Corresponding to the higher transition-metal content, the covalent network of platinum atoms is two-dimensional. The node connectivity in the network is three or four; the total coordination number of all platinum atoms is ten. Single layers of iodide ions separate the intermetallic layers. Two-thirds of the iodide ions are coordinating bismuth atoms that protrude from the intermetallic layer, forming [BiI4] squares. Temperature-dependent electrical resistivity and magnetic susceptibility measurements on polycrystalline powders indicate that Bi8Pt5I3 and Bi16Pt11I6 are diamagnetic metals. The calculated electronic band structures confirm pseudo two-dimensional metallic character only for Bi8Pt5I3.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bismuth; Covalent metals; Layered metals; Platinum; Subvalent compounds